Technology deposition of corrosion-resistant and scratch-resistant coating on the details of mining equipment - Platonova, E.S.; Buchinskas, V.; Jurov, V.M.; Laurinas, V.Ch. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
As it is shown experimentally that the technology greatly exceeds the vacuum nitriding zinc coatings. Along with this, the cost of such parts with coatings 10–15 % lower zinc. From the experimental data that the Fe–Al coating and Fe–Al–Ti can be used as corrosion-resistant, anti-friction coatings on low-grade steels. This increases the life of the components of these steels in 3–4 times. Compare the result of nanohardness (7.413 GPa) with known solid materials shows that nanohardness coating Cr–Mn–Si–Cu–Fe–Al is almost 2 times higher nanohardness titanium and close to the multi-layer film Ti/-C:Н. Comparing the measurement results with the microhardness of the coating Fe–Al, Fe–Al–Ti and other shows that the multilayer coating is significantly superior to the latter. After nitriding microhardness multilayer coating increases.
Тау-кен құрал-жабдықтар бөлшектерін өндіруде коррозияға төзімді тұндыру технологиясы мен сызаттарға төзімді жабындылар
Технология осаждения коррозионно-стойких и упрочняющих покрытий на детали горношахтного оборудования
Keywords: coating; nitriding; microhardness; nanohardness; corrosion resistance; heat resistance; friction